Peningkatan Kualitas Bio-Oil Hasil Pirolisis Cangkang Kelapa Sawit Berstandar Pelumas Organik - Wiraya, Wira Arta; Rifaldi, Kornelius; Muljani, Srie; Siswati, Nana Dyah; Karaman, Novel (Universitas Andalas, 2025)
Palm kernel shells are biomass waste that has the potential to be processed into bio-oil through pyrolysis, but its quality needs to be improved to meet organic lubricant standards. This study aims to improve the quality of bio-oil through a transesterification process with activated carbon-NaOH catalyst and the addition of guar gum as a thickening agent. Pyrolysis was carried out at a temperature of 300°C for 60 minutes, and transesterification at a temperature of 60°C for 2 hours with a methanol:bio-oil ratio of 6:1. The results showed that increasing the amount of catalyst up to 10% increased the yield of methyl ester, while the addition of guar gum increased the kinematic viscosity to 7.9 cst, approaching commercial lubricant standards such as top 1 Evo 5W-30 and pertamina fastron gold 5W-30. However, the flash point is still lower than industrial lubricants. Thus, the quality of bio-oil from palm kernel shell pyrolysis can be improved to approach organic lubricant standards, making it a more environmentally friendly alternative lubricant and has the potential for industrial applications.